Relasi Pemikiran Nabia Abbott dan Ignaz Goldziher dalam Studi al-Hadith - Muawanah, Arofatul (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2017)
Among the Orientalists, who have different ideas, are Ignaz Goldziher and Nabia Abbott. In his study, Goldziher always shows a sharp criticism of the scientific construction of hadith, and his views on hadith have been always dissimilar with scholars of hadith. He also alleges that the existence of hadith is no longer original. Abbott's thought of hadith, in contrast, tends to be moderate. Broadly speaking, Abbott's views seem to reinforce the thought of ulama al-Hadith. Abbott even acknowledges that the compilation of hadith has existed since the Prophet Muhammad's lifetime. In this context, it is interesting to note that Goldziher and Abbott are equally orientalists who employ the Western paradigm in examining hadith. The question is whether there is a relationship of thought between the two. Using descriptive and analytical methods this article specifically traces and explores the relationship of Abbott and Goldziher's thoughts. The study aims to determine the extent to which the relation of thought between the two orientalists and the factors that affect the similarity of thought between them.